Attributing Causes of Future Climate Change in the California Current System With Multimodel Downscaling. Issue 11 (5th November 2020) - Howard, Evan M.; Frenzel, Hartmut; Kessouri, Fayçal; Renault, Lionel; Bianchi, Daniele; McWilliams, James C.; Deutsch, Curtis
Abstract: Coastal winds in the California Current System (CCS) are credited with the high productivity of its planktonic ecosystem and the shallow hypoxic and corrosive waters that structure diverse macrofaunal habitats. These winds thus are considered a leading mediator of climate change impacts in the CCS and other Eastern Boundary Upwelling systems. We use an eddy‐permitting regional model to downscale the response of the CCS to three of the major distinct climate changes commonly projected by global Earth System Models: regional winds, ocean warming and stratification, and remote water chemical properties. An increase in alongshore winds intensifies spring upwelling across the CCS, but this response is muted by increased stratification, especially during summer. Despite the seasonal shift in regional wind‐driven upwelling, basin‐scale changes are the decisive factor in the response of marine ecosystem properties including temperature, nutrients, productivity, and oxygen. Downscaled temperature increases and dissolved oxygen decreases are broadly consistent with coarse resolution Earth System Models, and these projected changes are large and well constrained across the models, whereas nutrient and productivity changes are small compared to the intermodel spread. These results imply that global models with poor resolution of coastal processes nevertheless yield important information about the dominant climate impacts on coastal ecosystems. Key Points: We dynamically downscale the response of the California Current System to climate changes from five global Earth System Models Stratification and remote chemical properties, rather than regional winds, play a decisive role in coastal biogeochemistry changes Oxygen decreases and temperature increases are robust across downscaled models, but the nutrient and productivity changes are not